Transferencias monetarias estatales e intimidad: la dimensión moral del dinero en los hogares argentinos - Martín Hornes (Revista de Estudios Sociales, 2021)
This article proposes an approximation of the social and moral meanings that state money acquires in households holding cash transfer programs (TM). From an ethnographic field work carried out in popular neighborhoods of the Municipality of Avellaneda (Province of Buenos Aires of the Argentine Republic) a qualitative approximation of the budgets of different households is carried out, with the aim of demonstrating that the expansion and rooting of cash transfers programs transforms the family dynamics of the popular sectors. Indeed, this situation generates new power relations that are mobilized from disputes over social constructions of gender and intergenerational interpretations of the moral meanings that such money acquires.